Skrining Kesehatan Jiwa pada Ibu Hamil sudahkah diimplementasikan? - damayani, ayi diah; Harindra; Auronita Puspa Pertiwi; Akhiat; Intaglia Harsanti (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Midwifery care for pregnant women is carried out based on standards set by the government in Minister of Health Regulation no. 21 of 2021, as one of the strategies for reducing maternal mortality. Standards for antenatal care include 10 Ts, namely measurement of weight and height, measurement of blood pressure, measurement of upper arm circumference, measurement of the uterine fundus, fetal presentation and determination of fetal heart rate, examination and administration of tetanus vaccination, administration of blood supplement tablets, laboratory tests, management and interviews as well as mental health assessments. Objective: Analyze the implementation of the ANC 10 T standard in Bangka Belitung province.Method: Qualitative research, data collection was carried out by conducting interviews with 10 respondents and filling out questionnaires  with 124 pregnant women and 41 midwifes. The research was conducted in July – October 2023.Results: Of the 124 respondents, 57.3% of people stated that ANC services were according to standards, 10.5% were quite suitable and 32.3% were very suitable. Of the 41 midwifes, 48.8% said ANC services were very suitable, 34.1% said they were good and 14.6% said they were moderate, and 2.4% felt they were not appropriate in carrying out ANC. Conclusion: The 10 T ANC service standard has been implemented in all primary health services (Puskesmas) however technical instructions/screening regarding ANC services related to mental health have not been optimally implemented. Cross-sector coordination is needed to improve the quality of 10 T services.